Proceedings of Loops and Legs in Quantum Field Theory — PoS(LL2016) 2016
DOI: 10.22323/1.260.0058
|View full text |Cite
|
Sign up to set email alerts
|

Long-distance singularities in multi-leg scattering amplitudes

Abstract: We report on the recent completion of the three-loop calculation of the soft anomalous dimension in massless gauge-theory scattering amplitudes. This brings the state-of-the-art knowledge of long-distance singularities in multi-leg QCD amplitudes with any number of massless particles to three loops. The result displays some novel features: this is the first time non-dipole corrections appear, which directly correlate the colour and kinematic degrees of freedom of four coloured partons. We find that non-dipole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 59 publications
1
26
0
Order By: Relevance
“…Infrared singularities of massless scattering amplitudes are now fully known, for general colour, kinematics and any number of partons, through three loops, owing to an explicit computation of the soft anomalous dimension at this order [26,27]. While through two loops infrared singularities are governed exclusively by a sum over colour dipoles formed by pairs of the hard-scattered partons [28][29][30][31], at three loops one encounters for the first time infrared singularities that are simultaneously sensitive to the colour and kinematics of three and four hard partons.…”
Section: Jhep03(2018)098mentioning
confidence: 99%
See 3 more Smart Citations
“…Infrared singularities of massless scattering amplitudes are now fully known, for general colour, kinematics and any number of partons, through three loops, owing to an explicit computation of the soft anomalous dimension at this order [26,27]. While through two loops infrared singularities are governed exclusively by a sum over colour dipoles formed by pairs of the hard-scattered partons [28][29][30][31], at three loops one encounters for the first time infrared singularities that are simultaneously sensitive to the colour and kinematics of three and four hard partons.…”
Section: Jhep03(2018)098mentioning
confidence: 99%
“…It has been shown that the soft anomalous dimension has a simple dipole structure up to two loops [28]. Corrections involving three and four partons arise starting at three loops, and a series of analyses has been performed in order to constrain their structure at three loops and beyond [29][30][31][35][36][37]; the complete correction at three loops was calculated recently [26,27].…”
Section: Jhep03(2018)098mentioning
confidence: 99%
See 2 more Smart Citations
“…ref. [19] and references therein). The key quantity we wish to calculate is called the soft anomalous dimension Γ S , which controls the ultraviolet singularities of Wilson lines.…”
Section: Introductionmentioning
confidence: 99%